Edukasi dan Pelatihan Deteksi Dini Stunting Bagi Orang Tua dan Kader Kesehatan - majid, ana_majid; Wa Nuliana; Abuzar Wakano; Saidah Rauf (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2025)
Since 2018, Central Maluku Regency has had several sub-districts designated as national stunting loci. Based on data obtained at the Laimu Health Center during the integrated health post activities in April 2023, 11 children were identified as being at risk of stunting. To reduce this problem, efforts are needed that involve community participation, one of which is through education and training aimed at mothers and health cadres. Aims: to improve the knowledge and skills of mothers and cadres in carrying out early detection of stunting and how to prevent it. Method: Activities in the form of providing education, simulations and demonstrations on early detection and how to prevent stunting. Participants: 14 health cadres and 60 mothers of infants and toddlers in Lahakaba Village, Telutih District, Central Maluku. Results: activities showed an increase in the knowledge of health cadres and mothers of toddlers about early detection of stunting and how to prevent it as well as an increase in the skills of cadres on how to measure and assess stunted children. Through this activity, it is hoped that it can be sustainable and get support from related parties, especially the village government and health centers in overcoming stunting.